Generation of a Murine Model for c-MYC and BCL2 Co-expression B Cell Lymphomas - Cai, Zhenming; Zhang, Le; Cao, Min; Wang, Yuliang; Wang, Feng; Bian, Weiqi; Zhai, Sulan; Wang, Xiaoming (Frontiers in Oncology, 2020)
Diffuse large B-cell lymphoma (DLBCL) is the most frequent lymphoma in adults, and is characterized as clinically and biologically heterogeneous lymphomas with diverse response to therapy and variation in clinical behavior. It's well-established that c-MYC and BCL2 play important roles in normal B-cell differentiation and tumorigenesis. B cell lymphoma with dual expression of c-MYC and BCL2 (double-expressor lymphoma, DEL) accounts for approximately one-third of DLBCL cases. DEL patients have poor outcomes after chemoimmunotherapy or autologous stem-cell transplantation. Lack of a genetic mouse tool for DEL hinders us from understanding the lymphogenesis mechanism and developing therapeutic strategies. Here, we investigated whether ectopic expression of c-MYC and BCL2 in different stages of B cells could lead to lymphoma and generate a mouse model for DEL. We observed that Co-expression of c-MYC and BCL2 in germinal center (GC) B cells, or pan-B cells could induce B cell lymphomas. The tumor-bearing mice have enlarged lymphoid organs, and B cells massively infiltrate into non-lymphoid organs including lung, liver and kidney. The tumor-bearing mice also manifested significantly shorter lifespan than the controls. In addition, adoptive transfer of Co-expression B cells leads to B cell lymphoma and host mice death. This model will provide us a tool to further explore the pathogenesis and treatment approaches for DEL.